2014
DOI: 10.1158/0008-5472.can-12-4038
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial-Specific Notch Blockade Inhibits Vascular Function and Tumor Growth through an eNOS-Dependent Mechanism

Abstract: Notch signaling is important for tumor angiogenesis induced by vascular endothelial growth factor A. Blockade of the Notch ligand Dll4 inhibits tumor growth in a paradoxical way. Dll4 inhibition increases endothelial cell sprouting, but vessels show reduced perfusion. The reason for this lack of perfusion is not currently understood. Here we report that inhibition of Notch signaling in endothelial cell using an inducible binary transgenic system limits VEGFAdriven tumor growth and causes endothelial dysfunctio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 36 publications
3
28
0
1
Order By: Relevance
“…7b,c). Interestingly, previous studies showed that JAG1 stimulation could activate eNOS in the presence of VEGF 38 . In our system, we observed that eNOS promoter was activated by JAG1 overexpression (Fig.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…7b,c). Interestingly, previous studies showed that JAG1 stimulation could activate eNOS in the presence of VEGF 38 . In our system, we observed that eNOS promoter was activated by JAG1 overexpression (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…JAG1 is the upstream ligand of the Notch pathway and serves a much more complicated context-dependent role in regulating vascular activities 37, 38 . Upon recombinant JAG1 stimulation during differentiation, part of the endothelial markers, especially eNOS, could be induced to a higher level (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…NO produced by the NO-synthases may act as a pro-angiogenic factor in many cancers. Both endothelial and neuronal NO-synthases have been linked with metastasis [12] and modulation of several signaling pathways active in melanoma as Notch and Interferon [13]. Melanoma-cell derived NO is a crucial modulator of immune function in the tumor microenvironment and provides a potentially novel target for treatment [14].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, biochemical and functional analysis reveals that endothelial nitric oxide production is decreased by Notch inhibition, suggesting that lack of functional vessels observed with Notch inhibition is secondary to inhibition of nitric oxide signaling. Co-culture and tumor growth assays reveal that Notch-mediated nitric oxide production in ECs requires VEGFA signaling [320]. …”
Section: Specific Protein Kinases and Associated Signaling Pathwaymentioning
confidence: 99%